An appraisal of bacteriophages as biocontrol agent in treating E.coli O157:H7 mediated experimental gastroenteritis in mice - Mosharraf, Fahareen-Binta-; Ahsan, Chowdhury Rafiqul; Yasmin, Mahmuda; Nessa, Jamalun (© 2015 International Journal of Multidisciplinary Research and Development, 2016)
This article was published in the International Journal of Multidisciplinary Research and Development [© 2015] and The Journal's website is at: http://www.allsubjectjournal.com/archives/2015/vol2/issue4/66